Prototyping Advanced Control Systems on FPGA. (22nd June 2009) - Simard, Stéphane; Mailloux, Jean-Gabriel; Beguenane, Rachid
Abstract : In advanced digital control and mechatronics, FPGA-based systems on a chip (SoCs) promise to supplant older technologies, such as microcontrollers and DSPs. However, the tackling of FPGA technology by control specialists is complicated by the need for skilled hardware/software partitioning and design in order to match the performance requirements of more and more complex algorithms while minimizing cost. Currently, without adequate software support to provide a straightforward design flow, the amount of time and efforts required is prohibitive. In this paper, we discuss our choice, adaptation, and use of a rapid prototyping platform and design flow suitable for the design of on-chip motion controllers and other SoCs with a need for analog interfacing. The platform consists of a customized FPGA design for the Amirix AP1000 PCI FPGA board coupled with a multichannel analog I/O daughter card. The design flow uses Xilinx System Generator in Matlab/Simulink for system design and test, and Xilinx Platform Studio for SoC integration. This approach has been applied to the analysis, design, and hardware implementation of a vector controller for 3-phase AC induction motors. It also has contributed to the development of CMC's MEMS prototyping platform, now used by several Canadian laboratories.